2018
DOI: 10.1111/1467-9566.12777
|View full text |Cite
|
Sign up to set email alerts
|

The enduring legacy of black lung: environmental health and contested illness in Appalachia

Abstract: Over the past twenty years there has been a deadly resurgence of coal workers' pneumoconiosis (CWP), commonly known as black lung disease. While increased prevalence of the disease is alarming, these data only capture cases where CWP has been officially recognised. We argue that many more cases of the disease are going unreported. Drawing from contested environmental illness literature, we examine issues surrounding diagnostic uncertainty and medical surveillance. We draw from qualitative data on black lung th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…We have previously reported that participation in the part 90 option programme is low (14.4% of eligible miners exercise their job transfer option) and that miners in Central Appalachia are even less likely to exercise the option (13.1% vs 17.3% in other states) 27. This alone demonstrates that this element of secondary prevention is not living up to its intended purpose.…”
Section: Discussionmentioning
confidence: 95%
“…We have previously reported that participation in the part 90 option programme is low (14.4% of eligible miners exercise their job transfer option) and that miners in Central Appalachia are even less likely to exercise the option (13.1% vs 17.3% in other states) 27. This alone demonstrates that this element of secondary prevention is not living up to its intended purpose.…”
Section: Discussionmentioning
confidence: 95%
“…[34] Although secondary prevention was strengthened with the 2014 MSHA final rule and the subsequent NIOSH enhancements to medical screening for coal miners, [35,36] important challenges remain, including suboptimal participation in radiographic surveillance and in the Part 90 program. [37] In 2018, the U.S. Senate added an amendment to the 2019 federal budget [38] that required NIOSH to provide a report to Congress which "identifies and describes potential barriers that limit active and non-active coal miner participation" in the CWHSP. Through a public request for information (RFI) posted to the Federal Register, [39] NIOSH solicited and received feedback from a variety of stakeholders representing industry and labor interests.…”
Section: Secondary Prevention Of Pneumoconiosismentioning
confidence: 99%
“…In rural communities, this silence tends to be even more pervasive as there are often fewer employment opportunities and residents may defend the polluting industry simply because it impacts their own or loved ones' financial wellbeing (Brown and Kelley ; Freudenburg and Davidson ; Shriver and Bodenhamer ). The literature on environmental health activism and contested environmental illness provides the theoretical scaffolding for our analysis.…”
Section: Elite Contestation Of Environmental Illness Claimsmentioning
confidence: 99%
“…Analysts have found that the type of work, such as roof bolters (Cohen and Velho ), surface miners (Halldin et al 2015), small mine operators (Laney and Attfield ), and the depletion of seams (Petsonk, Rose, and Cohen ) has an impact on black lung, yet the isolation of the resurgence of black lung to central Appalachia remains a puzzle. Other research points to an “outlaw operator” issue as another explanation for the black lung problem in Appalachia (Shriver and Bodenhamer ). Our study provides important insights into the social drivers of the resurgence of black lung.…”
Section: Introductionmentioning
confidence: 99%